1992
DOI: 10.1159/000158946
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Analysis of Alpha-Adrenoceptor Interactions with the Myogenic Response in Resistance Vessels

Abstract: The interaction of alpha 1- and alpha 2-adrenoceptor constriction of isolated rat cremaster small arteries (mean diameter +/- SEM, 114 +/- 5 microns) with the myogenic mechanism was examined with in vitro videomicroscopy. Microdissected vessels were double-cannulated with glass micropipets in a tissue bath, and intraluminal pressure was set at 65 mm Hg baseline pressure. Norepinephrine (NE) concentration-response curves were obtained alone and in the presence of prazosin or rauwolscine to establish the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The observed response time in the range of 30 s is very similar to those observed by other authors in visualized arterioles in the hindlimb muscle of cats (25) and dogs (16,18) as well as in the cremaster muscle of rats (22,36). The direct comparison in the present study of the vascular responses in the renal and the hindlimb circulation in animals of the same strain (in 3 of them, also in the same individuals) clearly shows that there is a distinct difference in the time course of the myogenic response in these two vascular beds.…”
Section: Comparison With Hindlimb Vasculaturesupporting
confidence: 89%
“…The observed response time in the range of 30 s is very similar to those observed by other authors in visualized arterioles in the hindlimb muscle of cats (25) and dogs (16,18) as well as in the cremaster muscle of rats (22,36). The direct comparison in the present study of the vascular responses in the renal and the hindlimb circulation in animals of the same strain (in 3 of them, also in the same individuals) clearly shows that there is a distinct difference in the time course of the myogenic response in these two vascular beds.…”
Section: Comparison With Hindlimb Vasculaturesupporting
confidence: 89%
“…Concerning the myogenic response in vitro, it was observed that phenylephrine, an α " -adrenergic agonist, produced an augmentation of the myogenic response in rat femoral arteries [81] and in rat mesenteric arteries [76]. The degree of augmentation by α-adrenergic agonists was shown to depend on the type of α-receptor involved [86]. However, the non-selective α-adrenoceptor agonist noradrenaline did not change the myogenic response in dog renal arteries [38].…”
Section: The Myogenic Response -Implications For Its Role In the Intamentioning
confidence: 99%
“…The myogenic response of renal afferent arterioles of mice, rats, and dogs (internal ID: 8 -20 m) is often complete within 5-10 s, whereas in other vascular beds it ranges from ϳ10 -15 s for small cremaster muscle arterioles (15-25 m) (613, 613, 615) to 60 -120 s for larger mesenteric and cremaster arterioles (ϳ100 m) (303, 740, 1671) and up to 5 min for mesenteric arteries and skeletal muscle arterioles (Ͼ180 m) (243, 667,1002). This diversity is probably related to a specific set of VSMC mechanosensation-contraction signaling systems.…”
Section: Kinetics Of the Myogenic Responsementioning
confidence: 99%